2019
DOI: 10.1093/hmg/ddz209
|View full text |Cite
|
Sign up to set email alerts
|

Acute manganese treatment restores defective autophagic cargo loading in Huntington’s disease cell lines

Abstract: The molecular etiology linking the pathogenic mutations in the Huntingtin (Htt) gene with Huntington’s disease (HD) is unknown. Prior work suggests a role for Htt in neuronal autophagic function and mutant HTT protein disrupts autophagic cargo loading. Reductions in the bioavailability of the essential metal manganese (Mn) are seen in models of HD. Excess cellular Mn impacts autophagic function, but the target and molecular basis of these changes are unknown. Thus, we sought to determine if changes in cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…In parallel with lysosomal membrane permeabilization, another mechanism of Mn-induced regulated necrosis revealed at similar exposure doses in microglia involves complex events including DNA damage, AIF nuclear translocation, mitochondrial membrane permeabilization, and poly (ADP-ribose) polymerase 1 (PARP1)-dependent cell death, altogether referring to “parathanatos” [ 121 ]. Oppositely, in a range of 6.25–100 μM Mn was shown to induce autophagic flux in Huntington’s disease cell models resulting in autophagic sequestration of huntingtin (Htt) aggregates, thus possessing protective effect [ 122 ].…”
Section: Mn-induced Alterations In Subcellular and Multicellular Biologymentioning
confidence: 99%
“…In parallel with lysosomal membrane permeabilization, another mechanism of Mn-induced regulated necrosis revealed at similar exposure doses in microglia involves complex events including DNA damage, AIF nuclear translocation, mitochondrial membrane permeabilization, and poly (ADP-ribose) polymerase 1 (PARP1)-dependent cell death, altogether referring to “parathanatos” [ 121 ]. Oppositely, in a range of 6.25–100 μM Mn was shown to induce autophagic flux in Huntington’s disease cell models resulting in autophagic sequestration of huntingtin (Htt) aggregates, thus possessing protective effect [ 122 ].…”
Section: Mn-induced Alterations In Subcellular and Multicellular Biologymentioning
confidence: 99%
“…Finally, despite the fact that a novel interaction between Mn and HD was published nearly a decade ago [ 9 ], and numerous subsequent studies have noted the rescue of HD phenotypes by the reinstatement of bioavailable Mn [ 10 , 22 , 23 , 39 , 40 ], the cause of this reduced Mn bioavailability is still unknown. The results of this study provide a novel approach towards potentially identifying the culprit that causes Mn deficiency in HD.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic risk factors for early onset PD alter cellular susceptibility to Mn toxicity [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. At excessive levels, kinase activities of vital cellular signaling cascades, including autophagy and insulin signaling, are responsive to increased Mn bioavailability and linked to HD pathology [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the upregulation of these proteins by Mn can be the result of either increased autophagic flux or blocked autophagic clearance. An integrated approach to investigating autophagy would require a series of dynamic monitoring methodologies (most likely transfection of a plasmid encoding a tandem GFP-mCherry-LC3B fusion protein to evaluate autophagy flux) with pharmacological manipulation using positive modulators, such as melatonin or rapamycin (Rap), and negative modulators of autophagy, such as LY294002, chloroquine (CQ), bafilomycin A (BafA), or 3-methyladenine (3-MA) ( Bryan et al, 2019 ). In their research into Mn-induced neurotoxicity, Zhang and colleagues found that at an early stage of autophagy (4–12 h after injection of 1 mol/L MnCl 2 into the right striatum) in Mn-exposed rats, the adaptive activation of autophagy reflects transient protection against Mn-induced neurotoxicity.…”
Section: Overview Of Autophagymentioning
confidence: 99%
“…The increase in the level of p62 caused by Mn can be abrogated by PI3K inhibition (with LY294002) but is not changed by mTOR inhibition (with Rap), indicating that the Mn-induced increase in p62 is PI3K-dependent. Treatment with lysosomal autophagy inhibitors (namely, CQ and BafA) can cause the accumulation of LC3-II puncta and increase the net uptake of Mn, effectively attenuating defects in Mn-induced autophagy in ST Hdh Q111 cells ( Bryan et al, 2019 ). Melatonin/Rap enhances autophagy to retard Mn cytotoxicity by ameliorating lysosomal dysfunction in BV-2 cells ( Porte Alcon et al, 2020 ).…”
Section: Overview Of Autophagymentioning
confidence: 99%